Emerging Mechanisms of Innate Immunity and Their Translational Potential in Inflammatory Bowel Disease - Corridoni, Daniele; Chapman, Thomas; Ambrose, Tim; Simmons, Alison (Frontiers in Medicine, 2018)
Activation of the innate immune system through pattern-recognition receptor (PRR) signalling plays a pivotal role in the early induction of host defence following exposure to pathogens. Loss of intestinal innate immune regulation, leading to aberrant immune responses, has been implicated in the pathogenesis of inflammatory bowel disease (IBD). The precise role of PRRs in gut inflammation is not well understood, but considering their role as bacterial sensors and their genetic association with IBD, they likely contribute to dysregulated immune responses to the commensal microbiota. The purpose of this review is to evaluate the emerging functions of PRRs including their functional cross-talk, how they respond to mitochondrial damage, induce mitophagy or autophagy, and influence adaptive immune responses by interacting with the antigen presentation machinery. The review also summarises some of the recent attempts to harness these pathways for therapeutic approaches in intestinal inflammation.